Властивості конгломератів ZnO-Zn, вирощених на неполірованій підкладці Si методом карботермічного відновлення при швидкому сонячному випаровуванні - Kovalskyi, Y.O.; Karpyna, V.A.; Myroniuk, L.A.; Olifan, O.I.; Korichev, S.F.; Danylenko, I.M.; Starik, S.P.; Strelchuk, V.V.; Ievtushenko, A.I. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2026)
This paper presents the results of a study of ZnO-Zn conglomerates synthesised on unpolished silicon (Si) substrates by the rapid solar evaporation method of ZnO/C precursors with mass ratios of 2:1 and 1:3. The obtained samples were analysed using X-ray structural analysis, which confirmed the formation of a wurtzite-type ZnO crystalline phase and metallic Zn. Photoluminescence spectra revealed two characteristic peaks: a near band edge emission at ~380 nm, caused by exciton recombination, and an intense green band at ~522 nm associated with oxygen vacancies. Raman spectroscopy revealed a shift in the E? (high) mode, which characterizes the oscillation of the oxygen sublattice, from 437 to 427 cm–1, indicating an increase in the lattice period because of elastic stresses in the crystallites. Energy dispersive analysis showed the distribution of grown ZnO and Zn conglomerates. The photocatalytic properties, which were studied by degrading the model dye methyl orange under UV irradiation, showed better values in the case of ZnO-Zn conglomerate synthesis at a precursor concentration of ZnO/C as 1:3. The results obtained demonstrate the promise of using concentrated solar radiation for the synthesis and creation of materials with the desired properties using environmentally friendly, energy-independent technologies.